Genomic data of two bacillus and two pseudomonas strains isolated from the acid mine drainage site at Mamut Copper Mine, Ranau, Malaysia - Yi Yik Low; Grace Joy Wei Lie Chin; Collin G. Joseph; Baba Musta; Kenneth Francis Rodrigues (Elsevier Ltd, 2021)
The genomic data of four bacteria strains isolated from the abandoned Mamut Copper Mine, an Acid Mine Drainage (AMD) site is presented in this report. Two of these strains belong to the genus Bacillus , while the other two belong to the genus Pseudomonas. The draft genome size of Pseu- domonas sp. strain MCMY3 was 6,396,595 bp (GC: 63.3%), Bacillus sp. strain MCMY6 was 6,815,573 bp (GC: 35.2%), Bacillus sp. strain MCMY13 was 5,559,059 bp (GC: 35.5%) and Pseudomonas sp. strain MCMY15 was 7,381,777 bp (GC: 64.8%). These four genomes contained 4 93, 4 95, 4 95 and 579 annotated subsystems, respectively. The sequence data are available at GenBank sequence read archive with ac- cessions numbers SRX7859406, SRX7859404, SRX7859405 and SRX7293032 for strains MCMY3, MCMY6, MCMY13 and MCMY15, respectively.